ROLE OF SOCIAL SERVICES INCREASE IN BUSINESS RURAL COMMUNITY DEVELOPMENT IN VILLAGES MARANG - Miko, Seth (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2016)
The purpose of this research are: 1. Want to know the implementation of social services in the Village Marang. 2. Want to know the implementation of social services in rural community development in the village of Marang. 3. Want to know the role of social services in rural community development in the village of Marang.The type of research used is descriptive research, while the data collection was done by using questionnaires, interviews and documentation.In this study the hypothesis that made no use hypotheses that are commonly used in research but the form of questions that need answers from the research.From the data obtained the conclusion is:(1) With the implementation of social services in keluraÂ¬han Marang, all the respondents, 14 people (100%) ever get / obtain better services from the private sector / government agencies and by the local community.As for the form of social services: guidance and counseling related to livelihood / employment, health care, capital / money, material assistance / goods and messages of other development.While social services are rendered is in the village hall (hall Basarah) and the statement of 13 respondents (92.85%) stated on cooperation with local authorities (village chief and his staff).(2) It is known that the implementation of social services in rural community development in Marang village, namely:(A) That the majority of respondents, 13 people (92.86%) understand about social services gained.(B) By obtaining social services 11 (70.57%) are the perceived benefits, the changes are positive (building) for themselves and in the presence of such changes can increase revenue / income, which in turn can improve the welfare of her / family even local communities.(3) Can be known to result from respondents and supported by the results of the documentation, the role of social services in rural community development in Marang village is quite a role, while in outline the role that is shaped:(a) Guidance and counseling related to livelihood.(b) Health services.(c) Capital / money.(d) Assistance material / goods, and (e) other development messages